2022
DOI: 10.1080/20018525.2022.2097377
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms involved in the pathogenesis of airway remodeling in chronic lung disease

Abstract: Background Airway epithelial cells and lung fibroblasts play an important role in the development of chronic lung disease, but the exact mechanisms responsible have not been clarified. Our objective was to investigate the involvement of these cells in the inflammatory response associated to chronic lung disease. Methods Human lung fibroblasts and airway epithelial cells were challenged with Interleukin-1β and hypoxia, and with inhibitory (simvastatin) stimuli of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…Elevated glucose concentrations can stimulate bacterial interactions with the airway epithelium, 44 which may influence the development of COPD. Moreover, shared pathogenic mechanisms, such as chronic systemic inflammation, oxidative stress, and hypoxia, may contribute to this association 45,46 . We found that waist circumference was positively associated with risk of COPD, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Elevated glucose concentrations can stimulate bacterial interactions with the airway epithelium, 44 which may influence the development of COPD. Moreover, shared pathogenic mechanisms, such as chronic systemic inflammation, oxidative stress, and hypoxia, may contribute to this association 45,46 . We found that waist circumference was positively associated with risk of COPD, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, shared pathogenic mechanisms, such as chronic systemic inflammation, oxidative stress, and hypoxia, may contribute to this association. 45,46 We found that waist circumference was positively associated with risk of COPD, consistent with previous studies. A US cohort study 47 demonstrated that a greater waist circumference was positively associated with COPD.…”
Section: Discussionsupporting
confidence: 91%
“…COPD is diagnosed when the ratio of forceful expiratory volume in the first second to all expiratory volume (FEV1/FVC) is <70% 15 after inhalation of bronchodilators, indicating persistent airflow limitation, combined with the patient’s clinical presentation and the presence of high-risk factors such as smoking, dust or chemical irritation, infection, and the exclusion of other diseases. The common pathogenesis of COPD includes 16 , 17 chronic inflammatory mechanisms involving neutrophils, macrophages and lymphocytes; protease and anti-protease imbalance caused by an increase in protein hydrolases and a decrease in anti-protease; oxidative stress mechanisms and other mechanisms that increase oxidation beyond the body’s antioxidant capacity, leading to an oxidative and antioxidant imbalance. The conventional treatment of COPD is to improve the patient’s poor ventilation, get rid of sputum, control symptoms such as infection, protect lung function, improve the patient’s quality of life, slow down the progression of the disease and reduce death.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…The crucial role that resident cells play in the pathological progression of airway remodeling is becoming increasingly recognized. These cells, which include fibroblasts, macrophages, neutrophils, lymphocytes, mast cells, and Innate Lymphoid Cells (ILC), contribute to airway remodeling through the direct or indirect release of pivotal factors such as cytokines, proteases, and growth factors [ [4] , [5] , [6] ]. Despite these findings, the specific role of lung-resident cells in airway remodeling remains shrouded in uncertainty.…”
Section: Introductionmentioning
confidence: 99%